DDIS-17. DEVELOPMENT OF BRAIN-PENETRANT EGFR INHIBITORS FOR CNS MALIGNANCIES. (11th November 2019) - Tsang, Jonathan; Urner, Lorenz; Tse, Christopher; Baufeld, Lynn; Faull, Kym; Clark, Peter; Cloughesy, Timothy; Jung, Michael; Nathanson, David
Abstract: The epidermal growth factor receptor (EGFR) is altered in nearly 60% of glioblastoma (GBM) tumors, however, EGFR tyrosine kinase inhibitors (TKIs) have failed to improve outcomes for patients with GBM. This can be attributed to the inability of clinically available EGFR TKIs (e.g., erlotinib, gefitinib, lapatinib, afatinib, cetuximab) to effectively cross the blood-brain-barrier (BBB) and reach adequate pharmacological levels for a tumor response. Herein, we performed a structure-activity relationship (SAR) to obtain EGFR TKIs with both high brain penetrance and potency against EGFR-activated GBM cells. From over 80 novel compounds synthesized, our lead EGFR TKI—JCN068—exhibited exceptional BBB penetration (350% brain to plasma) while also having optimal ADME properties (60% oral bioavailability, 5 hr half-life, >100 µg/mL solubility, etc). Moreover, JCN068 demonstrated picomolar potency against purified EGFR kinase, 1000-fold selectivity for EGFR relative to other kinases, and nanomolar activity against EGFR-altered, GBM patient-derived cells in culture. Importantly, JCN068 demonstrated superior efficacy—with negligible toxicity—compared to clinically available small molecule EGFR TKIs (erlotinib and lapatinib) against multiple EGFR-altered patient-derived orthotopic GBM xenografts. Due to these excellent drug-like properties, JCN068 is currently progressing towards clinical development for EGFR-activated GBM patients.